Missed opportunities for preventing group B streptococcus infection. Issue 1 (12th May 2009) - Vergnano, S; Embleton, N; Collinson, A; Menson, E; Bedford Russell, A; Heath, P
Abstract : Background: Group B streptococcus (GBS) is the most common cause of early onset (EO) neonatal infection in the UK. National guidelines for its prevention were introduced in 2003. We assessed the opportunities for prevention amongst cases of EO GBS using the electronic Neonatal Infection Surveillance Network (NeonIN). Methods: Culture proven EO GBS cases occurring between 2004 and 2007 were identified prospectively in eight neonatal units participating in NeonIN. Data concerning risk factors, intrapartum antibiotic (IAP) use and infant outcome were collected retrospectively. Results: There were 48 cases of GBS over the 4 years (0.52/1000 live-births); 22 male, median gestation 38 weeks. The most common clinical presentation was sepsis and the GBS-attributable mortality was 6%. Risk factors were present in 67% (32) and adequate IAP was given to six of these mothers (19%). If all women with risk factors received prophylaxis, 23 cases (48%) may have been prevented. Conclusions: Better GBS prevention strategies are required in the UK.